2016
DOI: 10.1007/s00774-016-0759-6
|View full text |Cite
|
Sign up to set email alerts
|

The association between osteoporotic hip fractures and actinic lesions as a biomarker for cumulative sun exposure in older people—a retrospective case–control study in Argentina

Abstract: The aim of this study was to analyze the association between the presence of actinic lesions (solar keratosis and non-melanoma skin cancer) and osteoporotic hip fractures in older patients. Both pathologies are common conditions in this age group. Since cumulative sun exposure is difficult to quantify, the presence of actinic lesions can be used to indirectly analyze the association between ultraviolet radiation and osteoporotic hip fractures. This was an observational case-control study. We reviewed the centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“… 29 Of these, the greatest problem is hip fracture, which accounts for more than 20% of all orthopedic patients, 30 and the morbidity, mortality and economic costs of hip fractures are high, particularly in older individuals. 31 Research has shown that hip fracture is one of the most serious osteoporotic complications, 4 and one study showed that female aged 65 years or older who had their first hip fracture event were four times more likely to undergo subsequent episodes, compared to the general population. 32 Therefore, prevention of femoral fracture among fractures is important, which can be expected with greater sunlight exposure.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“… 29 Of these, the greatest problem is hip fracture, which accounts for more than 20% of all orthopedic patients, 30 and the morbidity, mortality and economic costs of hip fractures are high, particularly in older individuals. 31 Research has shown that hip fracture is one of the most serious osteoporotic complications, 4 and one study showed that female aged 65 years or older who had their first hip fracture event were four times more likely to undergo subsequent episodes, compared to the general population. 32 Therefore, prevention of femoral fracture among fractures is important, which can be expected with greater sunlight exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, UV exposure and sunlight absorption can differ significantly depending on geographic location, time of season and day, race, occupation, outdoor activity, lifestyle factors, and sunscreen usage. 4 In our study, we were unable to collect detailed information on the variables related to sun exposure because structured cross-sectional KNHANES data were used. Therefore, research should be conducted to minimize the effect of various ambient UV exposure levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The association between skin cancers, in particular MM, and OP is controversial; some studies claim that certain cancer types have been associated with an increased risk of fractures. However, melanoma and non-melanoma skin cancer were not associated with an increased risk of fractures, but rather a decrease because of major sun exposure and thus, potentially, a high average serum vitamin D level [99][100][101][102]. In contrast, others support the finding that VDR gene polymorphisms influence the risk of melanoma and that FokI F allele is associated with an increased risk of melanoma as well as the finding that Caucasian osteoporotic women with VDR FokI Ff genotype had lower femoral neck BMD than that in women with the VDR FokI FF genotype.…”
Section: Skin Cancersmentioning
confidence: 99%